A new vision of a classical question: How to become a mother?. (2nd January 2017) - Candilis-Huisman, Drina
Abstract: This article offers a reflection on conception, pregnancy, and the first mother–infant relationships of mothers with motoric and sensory disabilities. Based on more than 13 years of experience with women with motoric and sensory disabilities who had a desire for a child, the author analyzes this unusual situation from three different points of view: the medical help to procreate, meeting a partner for the mother, and the link with the initial maternal family, i.e. the mother's mother. The last part concerns the possibility of the development of a mother–infant relationship when bodily function is lacking.